Teaching and Practice in an Adult ICU: Experiences in a Nursing Internship Environment (Research, Society and Development, 2022)
Objective: The purpose of this study is to present the experiences of undergraduate nursing students during the practices developed in the HS in a university hospital in the capital Manaus-AM. Methodology: This study refers to an experience report, about the experiences of undergraduate nursing students of the Institute of Health and Biotechnology (ISB) of the Federal University of Amazonas (UFAM), during the course of the Supervised Curricular Internship (SCS) I. The same was developed in a University Hospital of high complexity in the adult ICU sector, in the period from November 18 to 20, 2019.  Results: The ESC in an adult ICU was of paramount importance for the teaching and learning of the nursing course students, where they had the opportunity to know the structure of the unit and even apply direct health care assistance to patients such as: cephalo caudal physical examination, installation of cushions, verification of vital signs, annotation and patient evolution. The experience acquired in this hospital environment has contributed significantly to the professional training of nurses. Final Considerations: The ECS is indispensable in the academic trajectory, since it allows contact with large hospital structures that have an ICU, where students have the opportunity to employ, in practice, the theory acquired in the classroom and, simultaneously, adding new knowledge.